2023
DOI: 10.3389/fpls.2023.1051840
|View full text |Cite
|
Sign up to set email alerts
|

Variability and genetic merits of white Guinea yam landraces in Nigeria

Abstract: IntroductionLandraces represent a significant gene pool of African cultivated white Guinea yam diversity. They could, therefore, serve as a potential donor of important traits such as resilience to stresses as well as food quality attributes that may be useful in modern yam breeding. This study assessed the pattern of genetic variability, quantitative trait loci (QTLs), alleles, and genetic merits of landraces, which could be exploited in breeding for more sustainable yam production in Africa.MethodsA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…The results delineated the possibility of indirect selection of traits that showed a positive correlation, such as yield and its related traits (plant vigor and number of tubers per plant) with tuber quality traits. A positive correlation between yield and yield related traits has also been reported by other researchers in yam (Agre et al [23], Adewumi et al [24], Adejumobi et al [46], Asfaw et al [49], Agre et al [35], and Padhan et al [52]). Similarly, a positive correlation was observed between dry matter content and the number of tubers per plant in all the families except for F4.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results delineated the possibility of indirect selection of traits that showed a positive correlation, such as yield and its related traits (plant vigor and number of tubers per plant) with tuber quality traits. A positive correlation between yield and yield related traits has also been reported by other researchers in yam (Agre et al [23], Adewumi et al [24], Adejumobi et al [46], Asfaw et al [49], Agre et al [35], and Padhan et al [52]). Similarly, a positive correlation was observed between dry matter content and the number of tubers per plant in all the families except for F4.…”
Section: Discussionsupporting
confidence: 76%
“…Olivoto and Nardino [18] compared several multi-trait selection indices and proposed the novel multi-trait genotype-ideotype distance index (MGIDI) to select genotypes with desirable mean performances across multiple traits while overcoming the limitations of traditional linear indices. The use of multiple traits in the selection of superior yam genotypes has been reported for D. rotundata wherein FAI-BLUP (multi-trait index-based factor analysis and ideotype design) [22] and MGIDI method [23] were used, while the MGIDI method was used for D. praehensilis [24] species, but none for D. alata species. In this context, an attempt was made in this study to assess a panel of D. alata mapping population progenies as well as their parents for selection of desirable genotypes/ideotypes based on their agronomic and quality characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The significant markers co-located with candidate genes for the evaluated traits could be essential for developing functional markers that would be useful for marker-assisted selection to enhance the development of D. praehensilis for post-harvest tuber quality traits. Detection of significant marker-trait association using GWAS has been reported in some yam species such as D. rotundata (Agre et al, 2021(Agre et al, , 2023 and D. alata (Gatarira et al, 2020;Mondo et al, 2021;Dossa et al, 2023) and other root and tuber crops such as cassava (Uchendu et al, 2021). This study detected putative candidate genes within the genomic regions of the target traits.…”
Section: Discussionmentioning
confidence: 59%
“…Many agronomic and tuber quality attributes have been studied using genome-wide association mapping in Dioscorea spp. These traits include tuber dry matter, tuber flesh color and oxidative browning in water yam (Gatarira Dossa et al, 2023), sex determination and crosscompatibility in water yam (Mondo et al, 2021), and tuber yield, tuber quality traits, yam mosaic virus resistance and sex determination and cross compatibility in white yam (Agre et al, 2021(Agre et al, , 2023Asfaw et al, 2022). This study identified seven significant markers for DMC on chromosomes 2, 3, 4, 5, 7, 17 and 19 and six significant marker for tuber flesh oxidation on chromosomes 3, 16, 17 and 19 (Table 2), which differed from SNPs identified by Gatarira et al (2020) on the two traits.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cultivated species, the white yam (Dioscorea rotundata) is popularly grown in West Africa, while the water yam (Dioscorea alata) has a global production outlook (Darkwa et al, 2020). Yam serves as a major source of food and income for many people along the yam value chain (Scott et al, 2000;Maikasuma and Ala, 2013;Agre et al, 2023). Yam has cultural, social, economic, and religious value in most African societies (Obidiegwu and Akpabio, 2017), as well as in most therapeutic potentials (Obidiegwu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%